Optimization of a Compton direct-charge detector for monitoring high-energy bremsstrahlung radiation - Nikiforov, V.I.; Shlyakhov, I.N.; Shevchenko, V.A.; Tenishev, A.Eh.; Uvarov, V.L. (Вопросы атомной науки и техники, 2019)
The conditions of application of a Compton direct-charge detector (DCD) for monitoring of intensity of the highenergy bremsstrahlung (X-ray) radiation are studied. A method is described for calculation of characteristics of the secondary е,Х-radiation at exit of an electron accelerator, and also for providing the conditions of the electronic equilibrium. By means of computer simulation, the processes of charge generation in a DCD monitor comprising two plates of different thickness from various metals are analyzed. On the basis of the obtained results, the requirements imposed on DCD composition for providing the maximum of its sensitivity are formulated. It is shown, that within the suggested DCD geometry, the monitor sensitivity reveals a weak dependence on the atomic number of its material at Z>29, and also on the end-point energy of X-rays in the span of 20…100 MeV.